Cognitive control network dysconnectivity and response to antipsychotic treatment in schizophrenia - Cadena, Elyse J. (Schizophr Res, 2018)
To better understand cognitive control impairment in schizophrenia, it is vital to determine the extent of dysfunctional connectivity in the associated fronto-striatal brain network, with a focus on the connections with the anterior cingulate cortex (ACC), prior to the potential confounding effect of medication. It is also essential to determine the effects following antipsychotic medication and the relationship of those effects on psychosis improvement. Twenty-two patients with schizophrenia, initially unmedicated and after a 6-week course of risperidone, and 20 matched healthy controls (HC) performed a fMRI task twice, six weeks apart. We investigated group and longitudinal differences in ACC-related functional connectivity during performance of a Stroop color task as well as connectivity patterns associated with improvement in psychosis symptoms. Unmedicated patients with schizophrenia showed greater functional connectivity between ACC and bilateral caudate and midbrain and lower connectivity with left putamen compared to healthy controls. At baseline, greater functional connectivity between ACC and bilateral putamen predicted subsequent better treatment response. Change in functional connectivity between ACC and left putamen positively correlated with better treatment response. These results suggest that patterns of functional connectivity in fronto-striatal networks can be utilized to predict potential response to antipsychotic medication. Prior to treatment, brain function may be structured with a predisposition that favors or not treatment response.